One-year follow-up of young people with ME/CFS following infectious mononucleosis by Epstein-Barr virus - Pricoco, Rafael; Meidel, Paulina; Hofberger, Tim; Zietemann, Hannah; Mueller, Yvonne; Wiehler, Katharina; Michel, Kaja; Paulick, Johannes; Leone, Ariane; Haegele, Matthias; Mayer-Huber, Sandra; Gerrer, Katrin; et al. (Frontiers in Pediatrics, 2024)
Follow-up studies on myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) in young people are rare and none have compared outcomes of adolescents and young adults with ME/CFS after confirmed Epstein-Barr virus-associated infectious mononucleosis (EBV-IM). Here we report on health trajectories of adolescents and young adults at 6 and 12 months after diagnosis of EBV-triggered ME/CFS, demonstrating that young adults experienced more severe symptoms, had poorer physical and mental functioning, and showed less favorable outcomes compared to adolescents. In sum, this study emphasizes the urgent need for early diagnosis of EBV-triggered ME/CFS in young people and for timely appropriate treatment.